Identification of Hydroquinone in Cosmetics Circulating in Kotamobagu City Using Chromatography Method - Bahi, Rizky Resvita R; Mappa, Moh Rivaldi; Hasan, Firja; Mokoginta, Warningsih (Journal of Experimental and Clinical Pharmacy (JECP), 2025)
The use of hazardous materials in facial whitening creams can endanger the health of users. Excessive use of hydroquinone can cause ochronosis, where the skin feels like it is burning and itching. Creams containing hydroquinone are widely circulated in the community and often cause undesirable effects. This study aims to analyze hydroquinone in cosmetics circulating in Kotamobagu City qualitatively using the Thin Layer Chromatography method. The results showed that the Rf value of the hydroquinone standard was 0.87 with a blackish brown stain color. Meanwhile, the Rf value and stain color of samples A, B, C, D and E were respectively 0.37 brownish yellow, 0.62 purple, 0.87 blackish brown, 0.75 blackish brown and 0.80 blackish brown. Based on the results of qualitative analysis using TLC, facial whitening cream cosmetics circulating in Kotamobagu City with samples A, B, C, D and E were positive for containing hydroquinone.